Enhancing West African family medicine curriculum through entrustable professional activities - Bolatito B. Fatusin; Musa Dankyau; Akye Essuman; Abraham N. Gyuse; Akinfemi J. Fatusin; Louis S. Jenkins (African Journal of Primary Health Care & Family Medicine)
The training of Family Medicine residents in the West Africa College of Physicians (WACP) has steadily upscaled to a competency-based approach over the years. The latest review of the curriculum (2022) includes self-directed online modules on clinical postings, health management, patient safety, quality assurance research and medical education among others. The operationalisation of the revised curriculum involves the use of workplace-based tools for formative assessments. However, some shortcomings of the traditional work place based assessment (WPBA) have been observed, including a lack of standardisation, time consumption, variability in the assessors’ judgements and systematic biases. These shortcomings can be mitigated through the adoption of entrustable professional activities (EPA) along with the use of WPBA.